Animal models for the study of liver fibrosis: new insights from knockout mouse models - Hayashi, Hiromitsu (American Physiological Society, 2011)
Fibrosis arises as part of a would-healing response that maintains organ structure and integrity following tissue damage but also contributes to a variety of human pathologies such as liver fibrosis. Liver fibrosis is an abnormal response of the liver to persistent injury with the excessive accumulation of collagenous extracellular matrices. Currently there is no effective treatment, and many patients end up with a progressive form of the disease, eventually requiring a liver transplant. The clarification of mechanisms underlying pathogenesis of liver fibrosis and the development of effective therapy are of clinical importance. Experimental animal models, in particular targeted gene knockouts (loss of function) in mice, have become a powerful resource to address the molecular mechanisms or significance of the targeted gene in hepatic functions and diseases. This review will focus on the recent advances in knowledge obtained from genetically engineered mice that provide novel insights into the pathophysiology of liver fibrosis.